Targeted theranostics of lung cancer: PD-L1-guided delivery of gold nanoprisms with chlorin e6 for enhanced imaging and photothermal/photodynamic therapy. (November 2020) - Liu, Bin; Qiao, Guanglei; Han, Yu; Shen, E; Alfranca, Gabriel; Tan, Haisong; Wang, Lirui; Pan, Shaojun; Ma, Lijun; Xiong, Wujun; Liu, Yanlei; Cui, Daxiang
Abstract: Peptide modified nanoparticles have emerged as powerful tools for enhanced cancer diagnosis and novel treatment strategies. Here, human programmed death-ligand 1 (PD-L1) peptides were used for the first time for the modification of gold nanoprisms (GNPs) to enhance targeting efficiency. A multifunctional nanoprobe was developed that the GNPs@PEG/Ce6-PD-L1 peptide (GNPs@PEG/Ce6-P) was used for imaging-guided photothermal/photodynamic therapy by using the targeting effect of PD-L1. Both confocal imaging and flow cytometry experiments demonstrated a remarkable affinity of the as-prepared nanoprobes GNPs@PEG/Ce6-P to lung cancer cells (HCC827), which have a high PD-L1 expression. Subsequent in vitro and in vivo experiments further demonstrated that the nanoprobes GNPs@PEG/Ce6-P not only allowed for real-time visualization via fluorescence (FL) imaging and photoacoustic (PA) imaging, but also served as phototherapy agents for synergistic photothermal therapy (PTT) and photodynamic therapy (PDT). Furthermore, treatments on human lung cancer cells-derived tumors demonstrated that the nanoprobes GNPs@PEG/Ce6-P could significantly suppress tumor growth through PTT and PDT from GNPs and Ce6, respectively. In conclusion, the as-prepared new nanoprobes show promising potential for nanomedicine with remarkable targeting ability for dual-mode imaging and enhanced PDT and PTT effects on lung cancer. Graphical abstract: Image, graphical abstract